ARE THE GINGIVAL DISPLAY AND THE SMILE ARC IN MALES AND FEMALES DIFFERENT? - Wita Anggraini; Indrani Sulistyowati; Annisaa Putri Ariyani; Stephany Alexandra (Majalah Biomorfologi, 2024)
Highlights Gingival display and smile arc enhance the aesthetic value of a person's smile and may be influenced through dental treatment. The individual profile photographs taken during social smiles can be used to evaluate dental treatment plans.   Abstract Background: An aesthetic smile is part of a person's attraction and affects their level of psychosocial well-being. Gingival display and smile arc belong to smile components that enhance the aesthetic value of a person's smile. Objective: To determine the differences in gingival display and smile arc in social smiles between males and females. Material and method: This analytical observational study was conducted with a cross-sectional design. A total of 110 photographs (55 males and 55 females) of study subjects who fulfilled the inclusion criteria were taken directly by Canon EOS-600D while performing social smile poses. The CorelDraw Graphic Suite 2022 measured gingival appearance and smile curves. The Chi-square test was performed to analyze the differences in gingival display and smile arc between males and females. Result: Based on gingival display, social smiles between genders were categorized into moderate (56.4% males and 58.2% females), low (30.9% males and 20% females), high (9.1% males and 18.2% females), and very high (3.6% males and females) smile lines. Social smiles based on smile arc were categorized into consonant (85.5% males and 96.4% females), straight (10.9% males and 3.6% females), and inverted (3.6% men and 0% women) smiles. No statistical differences were found in gingival display (p=0.397) or smile arc (p=0.113). Conclusion: There were no significant differences in gingival display or smile arc between males and females. Females, on the other hand, had an increased gingival show while smiling and no inverted smile arc.